Breaking the Equilibrium and Improving the Yield of Schiff Base Reactions by Pervaporation: Application to a Reaction Involving n-butylamine and Benzaldehyde - Rana Salem Al Khulaifi; Mohammed Mousa AlShehri; Inas Al-Qadsy; Mona A. Al Jufareen; Waseem Sharaf Saeed; Ahmed Yacine Badjah-Hadj-Ahmed; Taieb Aouak (Separations, 2023)
A comparative study of a Schiff base reaction involving benzaldehyde and n-butylamine was carried out to improve the yield of the resulting imine. This reaction was carried out at different temperatures without and with the elimination of the water produced during the process by the pervaporation (PV) technique using a typical cylindrical cell. To reach this goal, different dense membranes made of crosslinked poly(vinyl alcohol) with different oxalic acid (crosslinker) contents were prepared by the solvent casting method. Different parameters influencing the performance of the membrane in the separation process including swellability, diffusivity, crosslinking density, and thermal properties were investigated. The total and partial cumulative transmembranar fluxes as well as the separation factor were studied and the separation process was monitored by HPLC analysis. The n-butyl-1-phenylmethanimine produced was characterized by FTIR and 1HNMR analyses. The results obtained were a clear improvement in the yield of the reaction. For example, the yield obtained from the Schiff base reaction occurring without assistance by PV varied from 58 to 84 wt% when the temperature changed from 5 to 45 °C. On the other hand, when the PV process was used to eliminate water from this reaction mixture, the yield went from 90.4 to 98.6% by weight in this same temperature order. The cumulative total and partial fluxes significantly decreased with time. On the other hand, the separation factor reached a maximum at about one hour at 5, 15, and 45 °C. At 25 °C, the maximum total flux was reached at about 2 h of the PV process. The best selectivity of the PVA-0.5 membrane with regard to water was obtained at 15 °C. It was also revealed from the results obtained that the cumulative total and partial flux decreased rapidly with time and the separation factor reached a maximum at one hour into the PV process, in which 1.51 × 104 was reached at 15 °C, 6.25 × 103 and 3.50 × 103 at one hour of the separation process, and 10.23 × 103 at 25 °C at 2 h of the water removal by PV.